Factors That Influence Repurchase Interest At Chicken Pecel Restaurant In Jakarta - Salim, Agus; Mutiara Asya, Ina (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to analyze the influence of taste, service quality and shop atmosphere on repurchase interest among consumers of Warung Pecel Ayam Ibu Lasmi in South Jakarta. The method used in this research is descriptive quantitative and associative. The population in this study includes all consumers who make purchases at Warung Pecel Ayam Ibu Lasmi, the exact number of which is not known. The number of samples in this study was 100 respondents, with the criteria being consumers who had made purchases more than once. This research uses multiple linear regression analysis using IBM SPSS Statistics 26 software. The research results show that the better the taste, the greater the consumer's repurchase interest; the better the service quality, the higher the consumer's repurchase interest; The better the shop atmosphere, the greater the interest in repurchasing. These results indicate that there is a positive and significant influence on each variable partially on consumer repurchase interest.